KONTRIBUSI KEPEMIMPINAN VISIONER KEPALA SEKOLAH TERHADAP EFEKTIVITAS SEKOLAH DASAR NEGERI DI KECAMATAN KUTA RAJA KOTA BANDA ACEH - Zuriah, Cut; Sariakin, Sariakin; Putra, Mulia (LPPM Institut Pendidikan Nusantara Global, 2023)
An effective school has good management standards, is transparent, responsive and accountable. They are also able to empower every important element of the school, both internally and externally, to achieve the school's goals and vision. The research aims to determine the contribution of the school principal's visionary leadership to the effectiveness of State Elementary Schools in Kuta Raja District, Banda Aceh City. This research uses quantitative research methods with a description of the correlation method. The population in this study is all state elementary school (SD) teachers located in Kuta Raja sub-district, Banda Aceh City. The sample was taken by proportional random sampling of 36 people. Data was obtained by distributing questionnaires and then analyzed using the product moment test. The results of the research show that the correlation calculation between the principal's visionary leadership variable (X) and school effectiveness (Y) obtained a p value of 0.005 (P value 0.005 < α 0.05) so that the hypothesis was accepted. This means that the research hypothesis, namely that there is a positive and significant relationship between the school principal's visionary leadership and school effectiveness, has been tested.